The Role of Coaching Strategies and Training Programs in Developing Bowling Speed among Amateur Cricket Players (Journal of Social Sciences Review, 2025)
The aim of this research was to assess how power training and resistance affect medium-fast bowlers' bowling speed in cricket. Because of their capacity to create pace, medium-fast bowlers are vital in cricket; nevertheless, it's not known whether power training or resistance can really improve their bowling speed. This research included twenty medium-fast bowlers from cricket clubs of the Sports Board Punjab, aged between twenty and 25 years. Under a pre-test and post-test quasi-experimental design, bowling speeds were assessed using a speed gun both before and after an 8-week resistance and power training intervention. Emphasizing strength and plyometric activities meant to increase explosive power, the training sessions included moderate to high-intensity workouts. The mean speed of the participants improved significantly; from 118.75 km/h in the pre-test to 126.65 km/h in the post-test. A paired sample t-test revealed statistical relevance with a 0.000 p-value. A somewhat smaller range in bowling speed points to more consistent bowlers. Training was validated by pre-test and post-test speeds showing a modest positive correlation. The results imply that power and resistance training can increase the bowling speed of medium-fast bowlers, hence improving cricket performance. Bowlers were advised by coaches and trainers to include such drills to raise their performance. Long-term effects of this training on bowling speed and injury avoidance should be investigated in next studies.Keywords: Bowling Speed, Resistance Training, Power Training, Medium-Fast Bowlers.
Keywords: Bowling Speed; Resistance Training; Power Training; Medium-Fast Bowlers